A Class of Rigid Annular Disc Inclusion Problems Involving Translations and Rotations - Rogowski, B. (Engineering Transactions, 1986)
The paper considers the class of problems related to the annular inclusions located in an elastically supported layer. The layer is considered to be transversely isotropic and the inclusion is located on the plane of symmetry. The analysis is based on the potentia} functions referred to the cylindrical harmonics. The governing triple integral equations are solved by employing two approximate schemes: one focusses on the asymptotic expansion technique and the second focusses on the iterative series technique. The rotational and translational stiffnesses for the embedded annular disc inclusion, related to the displacement of the annulus in one of four ways: (i) translation and {!i) rotation in a direction normal to the piane face of the annulus; (iii) rotation and (iv) translation in a direction parallel to the face, are being investigated. The solutions of the special and limiting cases are also presented. Numerical calculations are carried out with some practical materials.